A review on borehole instability in active shale formations: Interactions, mechanisms and inhibitors - Gholami, Raoof; Elochukwu, H.; Fakhari, N.; Sarmadivaleh, Mohammad (Elsevier BV, 2018)
Shale formations are known for their chemical interactions with water based muds which may result in swelling, bit balling or even closure of the wellbore. As a result, eco-friendly water based fluids with inhibitive characteristics are required for drilling through shale formations. The aim of this study is to provide a deeper insight into drilling through shale formations by providing few approaches for different circumstances. Many inhibitors developed so far are introduced with their mechanism of shale inhibition presented. It appears that silicate based muds and thermally activated mud emulsion (TAME) are the best option to mitigate shale related issues, but more studies are required to provide a permanent solution for this very complicated issue, especially under HPHT conditions.